Pengaruh Promosi dan Saluran Distribusi Terhadap Brand Awareness dan Dampaknya Pada Minat Beli Kaos Kaki Champ - Sri Marini (Program Studi Administrasi Bisnis POLITEKNIK LP3I BANDUNG, 2019)
This study aims to obtain empirical evidence about the effect of promotion and channel distribution to the impact on brand awareness and purchase intentions socks champ . The results are expected to contribute in the development of marketing management , especially management . For those of similar companies and practitioners expected results of this study can provide useful information about the importance of the promotion , distribution channels and brand awareness in an effort to increase interest in purchasing . The study was conducted at 5 Borma department store branches in Bandung city . The method of research using survey methods with quantitative research approaches . While the type of research in the form of Descriptive Research and Research Explanation Verificative the time horizon in the form of cross - sectional data that reflects the picture of a state at a given moment . To test the hypothesis of statistical methods of research used path analysis. Test results of research found a significant relationship between promotion and distribution channels to brand awareness either simultaneously or partially . It was also found significant relationship between promotion , distribution channels and brand awareness to purchase intentions either simultaneously or partially.